ZnO Nanorods Coated Microfiber Loop Resonator For Relative Humidity Sensing - Adnan Zain, Huda; Jali, Mohd Hafiz; Md Johari, Md Ashadi; Mohd Yusof, Haziezol Helmi; Harun, Sulaiman Wadi; Abdul Rahim, Hazli Rafis; Thokchom, Siddharth; Yasin, Mohamad (Academic Press Inc., 2020)
This paper reported a new humidity sensor, employing microfiber loop resonator (MLR) coated with Zinc Oxide (ZnO) as a probe. The MLR was constructed from a silica tapered fiber with a waist diameter of 7 µm, which was prepared using flame brushing technique. The self-touching loop was coated by ZnO using sol–gel method. A significant response to humidity changes from 35%RH to 85%RH was observed due to the changeable refractive index of the ZnO coating material which modified the light propagation at the output of the MLR. The result shows that the sensitivity of the proposed sensor increases by a factor of 2 as compared to the uncoated MLR. The output power of the ZnO coated MLR drops linearly from −29.3 dBm to −43 dBm when relative humidity increases from 35%RH to 85%RH. The linearity and resolution of the ZnO coated MLR also outperformed the uncoated MLR with 99.4% and 0.013%RH respectively.